(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This study is devoted to improving the prevention of inflammatory complications in children after uranoplasty. Congenital cleft palate is one of the most common congenital anomalies of the maxillofacial region, and uranoplasty remains the main surgical method of treatment. In the postoperative period, inflammatory reactions, delayed wound healing, and suture dehiscence may occur, formation of a hematoma in the wound area. The study involved 30 patients who underwent uranoplasty. The patients were divided into two groups: a control group (15 patients) and a main group (15 patients). In addition to standard postoperative treatment, patients in the main group received magnetotherapy sessions. The results showed that the use of magnetotherapy reduced postoperative edema and hyperemia, accelerated wound healing, and significantly decreased the incidence of postoperative complications. The findings indicate that magnetotherapy can be considered an effective adjunct method for preventing inflammatory complications after uranoplasty in children.